Mental Health and Aggression in Indonesian Women - Aryati Hamzy; Cheng-Chung Chen; Kuan-Ying Hsieh (Behavioral Sciences, 2023)
Aggression is a global problem and complex social behavior. In Indonesia, some common manifestations of aggression are sexual harassment, domestic violence, and the stigmatization of other people. However, unlike men, aggression in women is still rarely studied, whereas facts find that many conditions can make women more vulnerable. There are various aspects related to biological, psychological, social, and cultural issues that can potentially provoke female aggression. Furthermore, mental health and aggression are often viewed as an automatic association and are inseparable in society, reinforcing the stigma against people with mental problems, particularly women, who tend to suffer more stigma of mental health issues than men. However, there has not yet been a study explicitly related to this relationship in the general population of women. The current study aims to examine the overall relationship between mental health and aggression in the extensive general population of Indonesian women with various mental conditions ranging from a normal mental state to severe mental health problems. This was a cross-sectional study conducted using uncontrolled quota sampling via distributing online self-report questionnaires, the modified Indonesian version instruments of the Brief Symptoms Rating Scale-5, and the Buss Aggression Scale with high internal consistency. This study among 203 women aged 19–67 in Indonesia, a multicultural nation and the fourth densest country in the world, proposes that mental health can be a predictor of aggressive behavior, with the influence of mental health on the aggression of women being 21.6% only. The finding indicates that mental health issues are not a macro contributing factor to women’s aggressiveness in society and may help reduce stigma against women with mental health problems.